Sentencing and punishment - Easton, Susan (Oxford University Press, 2008)
The second edition of this innovative text provides an accessible account of recent developments in sentencing and punishment from the standpoint of penal theories, policy aims, punishment practice and human rights. It reviews - from philosophical, legal and practical perspectives - changing ideas as to what counts as 'just' punishment, and provides an integrated discussion of the law and legitimacy of the process of calculating and implementing punishment